Development of polymeric nanofibers blended with extract of neem (Azadirachta indica), for potential biomedical applications - Hameed, Arruje; Rehman, Touseef Ur; Rehan, Zulfiqar Ahmad; Noreen, Razia; Iqbal, Sarosh; Batool, Shaheera; Qayyum, Muhammad Abdul; Ahmed, Toheed; Farooq, Tahir (Frontiers in Materials, 2022)
In recent years, electrospinning has emerged as a promising technique for the preparation of nanofibers with unique properties like flexibility, high porosity and high surface area. In the context of nanodelivery systems, polymer-based nanofibers have become promising carriers of drugs and bioactive compounds ensuring their sustained release and targeted delivery. In this study, neem extract-loaded nanofibers were developed as sustained delivery systems using the electrospinning method. The chitosan, alginate and polyethylene oxide were used as the polymeric matrix for loading of aqueous extract of neem leaves. The prepared nanofibers NF1, NF2 and NF3 carrying 2%, 4% and 6% extract respectively were characterized using SEM, FTIR, XRD and TGA. Further, the as-prepared nanocomposites exhibited a high degree of swelling and dual-phase release of phytoconstituents. Moreover, the developed controlled delivery systems were tested for antifungal and antioxidant potential. Importantly, the bioactivities of the prepared nanofibers could be improved further by using organic extracts which are generally enriched with phytoconstituents. Herein, we selected biodegradable and mucoadhesive biopolymers and an aqueous extract of neem for the development of controlled-delivery nanofibers by electrospinning through a sustainable and cleaner production process. Thus, the prepared biocompatible nanofibrous systems with biphasic release profile could be employed for biomedical applications including wound dressing, soft tissue scaffolds and as transdermal carriers.